Robustness of Representative Signals Relative to Data Loss Using Atlas-Based Parcellations - Gajdoš, Martin; Výtvarová, Eva; Fousek, Jan; Lamoš, Martin; Mikl, Michal (Brain topography, 2018)
Parcellation-based approaches are an important part of functional magnetic resonance imaging data analysis. They are a necessary processing step for sorting data in structurally or functionally homogenous regions. Real functional magnetic resonance imaging datasets usually do not cover the atlas template completely; they are often spatially constrained due to the physical limitations of MR sequence settings, the inter-individual variability in brain shape, etc. When using a parcellation template, many regions are not completely covered by actual data. This paper addresses the issue of the area coverage required in real data in order to reliably estimate the representative signal and the influence of this kind of data loss on network analysis metrics. We demonstrate this issue on four datasets using four different widely used parcellation templates. We used two erosion approaches to simulate data loss on the whole-brain level and the ROI-specific level. Our results show that changes in ROI coverage have a systematic influence on network measures. Based on the results of our analysis, we recommend controlling the ROI coverage and retaining at least 60% of the area in order to ensure at least 80% of explained variance of the original signal.
Keywords: dospělí; Healthy Volunteers; Magnetic Resonance Imaging; funkční lateralita; Female; Brain Mapping; Adult; počítačová simulace; Functional Laterality; ženské pohlaví; mladý dospělý; atlasy jako téma; Linear Models; Reproducibility of Results; zdraví dobrovolníci pro lékařské studie; lidé; magnetická rezonanční tomografie; světelná stimulace; mapování mozku; mozek; lineární modely; Photic Stimulation; Algorithms; Computer Simulation; reprodukovatelnost výsledků; Male; počítačové zpracování obrazu; Individuality; Brain; Young Adult; Atlases as Topic; algoritmy; individualita; mužské pohlaví; Image Processing, Computer-Assisted; Humans